New Media, Professional Sport and Political Economy. (December 2014) - Dart, Jon
New media technologies are seen to be changing the production, delivery and consumption of professional sports and creating a new dynamic between sports fans, athletes, clubs, governing bodies and the mainstream media. However, as Bellamy and McChesney (2011) have pointed out, advances in digital technologies are taking place within social, political, and economic contexts that are strongly conditioning the course and shape of this communication revolution. This essay assesses the first wave of research on professional sport and new media technologies and concludes that early trends indicate the continuation of existing neoliberal capitalist tendencies within professional sport. Using the concept of political economy, the essay explores issues of ownership, structure, production and delivery of sport. Discussion focuses on the opportunities sports fans now have available to them and how sports organization and media corporations shifted from an initial position of uncertainty, that bordered on hostility, to one which has seen them embrace new media technologies as powerful marketing tools. The essay concludes by stating as fundamental the issues of ownership and control and advocates that greater cognizance be accorded to underlying economic structures and the enduring, all-pervasive power of neoliberal capitalism and its impact in professional sport.